Students’ Perception on the Causes and Effects of English Speaking Anxiety - Arsy Aqilah Ramadanis; Nailul Authar (Universitas Nurul Jadid, 2026)
This study addresses the significant issue of English speaking anxiety among students, which affects their language learning and communication skills. Despite various studies on this topic, there remains a discrepancy between theoretical strategies and their practical application in classrooms. This research aims to explore students’ perceptions of the causes and effects of English speaking anxiety and the strategies used by teachers to overcome it in class IX-C of Rahmat Surabaya Junior High School. Employing a descriptive qualitative method, data were collected through observations and semi-structured interviews. The findings show that most students experience speaking anxiety primarily due to fear of making mistakes, concern about negative feedback, and low self-confidence. Anxiety symptoms are evident physically (trembling hands, sweating, increased heart rate), cognitively (difficulty thinking clearly, forgetting words), and behaviorally (avoiding eye contact, reluctance to speak in public). These symptoms significantly affect students’ classroom participation and self-confidence. To mitigate anxiety, teachers use strategies such as offering regular speaking opportunities, providing positive feedback, modifying learning activities to be more engaging, and applying relaxation techniques before speaking tasks. Peer support also contributes to lowering anxiety levels. The study concludes that creating a supportive and psychologically safe learning environment is essential for improving students’ English speaking competence. These findings provide valuable insights for educators and schools in developing more effective, inclusive strategies to address speaking anxiety in English classes.